PERSEPSI SISWA TERHADAP PEMBELAJARAN DARING PADA PELAJARAN MATEMATIKA - Restu Ayu Gustianingum; Yenita Roza; Maimunah Maimunah (HISTOGRAM: Jurnal Pendidikan Matematika, 2021)
The Covid-19 pandemic caused a change in the learning process from face-to-face learning to online learning. This article aims to present the perceptions of MAN students regarding online learning in Pekanbaru City. This type of research is qualitative research. Data collection in this study was carried out by giving a questionnaire with the help of google form and interviews. Samples were randomly selected of 347 students throughout the city of Pekanbaru. Students are given a questionnaire that has been tested for validity and reliability. he results showed that the students tended to give a positive perception that was 59%. However, students gave negative perceptions on several indicators such as technical indicators and the learning process. This shows that there are obstacles faced by students during online learning, especially in mathematics.